Manajemen Strategik Implementasi Program Pendidikan Merdeka Belajar - Putra, Karantioano S; Asyari, Lutfi; Rohani; Widyaningsih, Yennie Indriati (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract Strategic management of the implementation independent learning program. It is a library research with analytical descriptive qualitative method, aims to collect data or information by tracing various data in the form of online documents, articles, journals, books, laws, regulations, guidelines, and notes which are then analyzed using an educational approach. The results of the study, the strategic elements of the Independent Learning Education policy include: The independent learning paradigm, main policies, main targets and focus, priority program activities, challenges and implementation problems. The strategic management component in the implementation of the Independent Learning Education policy includes: principles of strategic management implementation, strategic management model, formulation of implementation strategies, steps to formulate strategic plans, and elements of strategic plan implementation. The objectives of implementing the independent learning education program are through the implementation of strategic management, which include: Improving the quality of education, ensuring the quality of education, and sustaining program development.